Reality is broken: why games make us better and how they can change the world - McGonigal, Jane
Visionary game designer Jane McGonigal shows how we can harness the power of computer games to solve real-world problems and boost global happiness, since her research suggests that gamers are expert problem solvers and collaborators because they regularly cooperate with other players to overcome daunting virtual challenges